Corruption and fraud detection through foresic accounting practices in kurdistan region of iraq - Subhi Mohamed Saleh; Zubir Azhar; Bayan Sedeeq Azeez (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This paper aims to explore the importance and the role of forensic accounting practices in detecting (and preventing) corruption and fraud; and to identify the factors that hinder the adoption of forensic accounting practices in Kurdistan Region, Iraq. To achieve the objectives of the study was developed questionnaire included (24 questions) distributed on 47 academic professionals in the Kurdistan Region Iraq, the researchers reached a number of conclusions after analyzing questionnaire’s questions. The most important of these conclusions There is a role Forensic Accounting in combating fraud and financial corruption in the Kurdistan Region and there are many factors that hinder the application of Forensic Accounting in the Kurdistan Region. The researchers also made a number of recommendations, in view of the importance of Forensic Accounting, therefore, researchers recommend increasing interest in it in the school curriculum and incorporating this aspect in accounting education so that the graduate to be familiar with it and the necessity for the Kurdistan Regional Government to build an effective monitoring system based on Forensic Accounting services that takes it upon itself to preserve both the rights and the financial authority.